A highly facile and selective Chemo-Paper-Sensor (CPS) for detection of strontium. (June 2016) - Kang, Sung-Min; Jang, Sung-Chan; Huh, Yun Suk; Lee, Chang-Soo; Roh, Changhyun
Abstract: Chemosensors have attracted increasing attention for their usefulness on-site detection and monitoring. In this study, we elucidated a novel, facile, and highly selective Chemo-Paper-Sensor (CPS) for detection and monitoring of strontium (Sr 2+ ) ions, which means a potent colorimetric sensor based on a Chrysoidine G (CG)-coated paper strip. The CPS for highly selective colorimetric detection of strontium ion was handily analyzed to determine the red-green-blue (RGB) value using portable devices such as desktop digital scanner and mobile phone camera, quantitatively. Interestingly, an orange to dark orange color transition was observed when the aqueous and solid paper colorimetric sensor was introduced to Sr 2+ ion, respectively. It was demonstrated that the value of the signal has a linear relationship with concentrations of the strontium in the 500 ppm to 100 ppb range with a detection limit of 200 ppb. We believe that a newly developed Chemo-Paper-Sensor will be useful in a wide range of sensing applications. Highlights: Paper-based colorimetric assay for detection of strontium ion was developed. Chemo-Paper-Sensor (CPS) provides a fast and simple naked-eye detection for strontium. CPS as a paper strip was cost-effectively fabricated. CPS toward strontium ion provides a high performance on-site detection and monitoring. CPS toward strontium was evaluated by using a portable device.